Adaptive finite time fault tolerant control for the quadrotor unmanned aerial vehicles based on time‐triggered strategy. (29th July 2022) - Di, Wangyue; Li, Zhigang; Lv, Dongyi; Gao, Chuang; Yang, Yonghui; Zhou, Xin
Abstract: This article investigates the adaptive finite time tracking control problem for quadrotor unmanned aerial vehicles (QUAV) subject to actuator failure with event‐triggered control strategy. It is assumed that the models of actuator failure are actuator blockage and saturation faults. The finite time performance function and adaptive backstepping method are combined to design the controller to compensate the influence of actuator failure, so as to ensure that the tracking error converges to the preset neighborhood near the origin in finite time. In addition, a new event‐triggered strategy is introduced to save communication resources and avoid the Zeno‐behavior, which defines the variable threshold as a function combining with tracking error and positive constants. The variable threshold not only effectively reduces triggering times, but also makes the design of the controller more flexible. It is proved that the closed‐loop system is stability. Finally, the effectiveness of this method is verified by simulation.